2020
DOI: 10.1145/3411560.3412835
|View full text |Cite
|
Sign up to set email alerts
|

Facing Global Health Crises Using Mobile Communications: An international virtual exchange experience

Abstract: This work reports on an international virtual exchange experience based on a digital health discipline that embedded a shared module with curricula addressing mobile communications to face health crises. This course took place in the context of COIL through a partnership between the Federal University of Pernambuco and the SUNY Downstate School of Public Health. The purpose of the experience was for students to develop skills to collaborate in teams made up of health professionals from different countries. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As explained in the previous section, students engage in polymedia practices when negotiating to learn using mobile communication, translated into the various mobile communication platforms they use, all of which are digital tools for collaboration. Maximizing the use of these platforms for collaboration can lead to more effective results, as reported in previous research on virtual exchange to increase collaboration (Barreto Belian et al, 2020b).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…As explained in the previous section, students engage in polymedia practices when negotiating to learn using mobile communication, translated into the various mobile communication platforms they use, all of which are digital tools for collaboration. Maximizing the use of these platforms for collaboration can lead to more effective results, as reported in previous research on virtual exchange to increase collaboration (Barreto Belian et al, 2020b).…”
Section: Resultsmentioning
confidence: 58%
“…Mobile communication is unavoidable to be embedded in student learning in the wake of the Covid-19 pandemic (Naciri et al, 2020). A prior study suggested that virtual exchange was mainly aimed at fostering students' multicultural collaboration skills, focusing on coping with a health crisis (Barreto Belian et al, 2020a). The results were that the program positively impacted everyone, but there were also the challenges of difficulties in engagement.…”
Section: Pengalaman Komunikasi Mobile Mahasiswa Dalam Program Pertuka...mentioning
confidence: 99%
“…Our sample population was derived from healthcare students participating in COIL, consisting of a partnership between the Federal University of Pernambuco located in Recife in northeast Brazil and the SUNY DHSU School of Public Health located in Brooklyn, New York in the United States [4].…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…In this sense, higher education courses for healthcare students need to be deeply transformed to comprehend and deal with worldwide problems, regarding local, regional, and global contexts [1,3]. Moreover, societal and cultural influences add to the challenges of interactivity promoted by globalization [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation